Web-based conference management system for higher learning institutions - Ahmad, Kamsiah; Abdullah, Aimi Amirah; Zeki, Akram M. (2012)
This study is about Conference Management Online System which provides an easier way of managing events when conducting a conference. The system will be specifically built for the convenience of Event Manager in managing online submission of papers and procedures with relation to the Event Manager himself, Reviewers and Authors. Besides that, this system is being proposed due to the lack of Conference Management Online System built especially for a university. This study would not only focus on the development process of the Conference Management Online System but it would also summarizes current system which are in use, design analysis of the new system which will include the flowchart of the systems and requirements needed in order to develop the system.